Indios contra encomenderos en tierra de frontera. Antioquia a inicios del siglo XVII (2014)
ABSTRACT: The article shows how indians took advantage of the “visita a la tierra” to change their fate in the oppressive reality of the encomienda. The statements by some indians of Antioquia to the oidor Herrera Campuzano (1614-1616), reveal they knew it was a form of control over the encomenderos. An effective argument was denounce the lack of proper christianization and spanish permissiveness respect to prehispanic beliefs involving the devil. This reveals two opposite views of the world, society and religious universe, expressed through indigenous reactions against the actions of the encomenderos.